Improving Makhorijul Letters through the Sorogan Method - Marwah Sopha; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2022)
Reading the Qur'an is a noble practice. Before reading the Koran, we must study makhraj and tajwid well so that we can read the Koran fluently, properly and correctly. Most of the TPA RT children. 11 Maracang Babakan Cikao village is not optimal in pronouncing hijaiyah letters when reading the Koran. The large number of children and limited teaching time and the ability of teachers make TPA activities less than optimal and children experience a lack of insight and knowledge about the science of makhorijul letters. The approach method used in this activity is by giving the theory of understanding of the Sorogan Method. This is done because one way is to listen directly and check understanding and correct the pronunciation of hijaiyah letters for TP A children Nur Maracang Village Rt.11 Babakan Cikao. This research also focuses on the application of the sorogan method in learning to read makharijul letters and whether there is an increase in the ability to read makharijul letters after using the Sorogan method . The method used in this study is the PAR (Participatory Action Research) approach . The results of this study are that the application of the sorogan method is carried out in groups and students experience an increase in the ability to read the Qur'an through the introduction of makhorijul letters through the sorogan method. This research has an impact on increasing students' ability to read the Qur'an. Students learn to read the Qur'an easily through the sorogan method.